Allergic rhinitis and pharmacological management in elite athletes - Alaranta, A.; Alaranta, H.; Heliovaara, M.; Alha, P.; Palmu, P.; Helenius, I. (Medicine & Science in Sports & Exercise, 2005)
Introduction: Only a few studies have examined the occurrence of atopy and clinically apparent allergic disease and their pharmacological management in elite athletes. The aim of the study was to assess the frequency of allergic rhinitis and the use of antiallergic medication within the subgroups of elite athletes as compared with a representative sample of young adults of the same age.